The making of science and technology policy in China. (1st January 2001) - Baark, Erik
This paper examines the conceptual changes and policy initiatives shaping China's science and technology (S&T) policy reforms. Using a taxonomy of four S&T policy cultures (bureaucratic, economic, academic, and civic), the paper explores the various tensions and compromises that have characterised the formulation and implementation of policies in the early 1980s. The process of policy making is then illustrated by reference to the reforms introduced during the last two decades in order to increase and diversify the funding of S&T activities in China.